Legalitas dan Prosedur Penyitaan Aset Virtual dalam Perkara Pidana di Indonesia: Tantangan Eksekusi pada Penyelenggara Perdagangan Aset Kripto Terdaftar - Putra, Samudra Farasi; Wahyudi, Slamet Tri (CV. Akira Java Bulu, 2026)
This research aims to analyze the legality and procedures for seizing virtual assets in criminal cases in Indonesia and identify execution challenges for Registered Crypto Asset Traders. The transformation of national criminal law through Law No. 1 of 2023 shifts the paradigm towards corrective justice emphasizing asset recovery, yet digital asset technology creates new juridical complexities. The research method used is normative juridical with a statutory and conceptual approach through literature study techniques. The results show a procedural legal vacuum in Law No. 20 of 2025 on the Criminal Procedure Code, which is still based on the physical asset paradigm, thus failing to reach decentralized digital asset characteristics. Although Law No. 4 of 2023 and OJK Regulation No. 23 of 2025 recognize crypto as a digital financial asset, its position in corporate capital structures under Law No. 40 of 2007 remains ambiguous. The main execution hurdles lie in extreme price volatility and the absence of technical protocols for investigators to gain digital access. This study recommends a seizure concept through a mechanism of converting virtual asset values into Rupiah at the time of seizure to lock the asset's economic value. This step is crucial to provide legal certainty for the state in recovering losses and protecting the defendant's rights from asset value depreciation during the judicial process. Therefore, regulatory synchronization between criminal procedure law and digital financial sector law is an absolute prerequisite for effective economic law enforcement in the digital era.